Biodegradation and kinetic study of benzene in bioreactor packed with PUF and alginate beads and immobilized with Bacillus sp. M3 - Kureel M.K.; Geed S.R.; Giri B.S.; Rai B.N.; Singh R.S. (My University, 2025)
Benzene removal in free and immobilized cells on polyurethane foam (PUF) and polyvinyl alcohol (PVA)-alginate beads was studied using an indigenous soil bacterium Bacillus sp. M3 isolated from petroleum-contaminated soil. The important process parameters (pH, temperature and inoculums size) were optimized and found to be 7, 37 °C and 6.0 × 108 CFU/mL, respectively. Benzene removals were observed to be 70, 84 and 90% within 9 days in a free cell, immobilized PVA-alginate beads and PUF, respectively under optimum operating conditions. FT-IR and GC–MS analysis confirm the presence of phenol, 1,2-benzenediol, hydroquinone and benzoate as metabolites. The important kinetic parameter ratios (µmax/Ks; L/mg·day) calculated using Monod model was found to be 0.00123 for free cell, 0.00159 for immobilized alginate beads and 0.002016 for immobilized PUF. Similarly inhibition constants (Ki; mg/L) calculated using Andrew-Haldane model was found to be 435.84 for free cell, 664.25 for immobilized alginate beads and 724.93 for immobilized PUF. © 2017 Elsevier Ltd